The Effectiveness of Early Mobilization on Post Sectio Caesarea Wound Healing - Anggraeni, Widya; Idayanti, Titiek; Fauziyah, Rahma (Jurnal MIDPRO, 2023)
Most mothers with post partumsectiocesaria feel worried if her body is moved in certain positions will affect post surgery wound that still hasn't fully recouered, also due to the pain that is felt after anesthesia effects is disapparing 1.. The purpose of this study was to determine the effectiveness of early mobilization wound healing post sectiocaesaria. The type of this research is analytic cross-sectional. Variabel in this research is mobilization as the independent variable and wound healing post sectiocaesarea as the dependent variable. The population of this research that is the entire women post sectiocaesarea on midwifery room Â as many as 85 mother. The results showed thatâ€™s from 31 respondents did proper mobilization well as many as of 28 respondents (55%) who ware healing fast and 3 respondents (9.7%) are healing slowly. T test test results obtained results of Ï = 0.00, Î± = 0.05. Then the Mean Î±. Ï < H0 was rejected and the H1 was accepted so there are influences of early mobilization with wound healing.Discuss: There is a relationship between early mobilization and wound healing. In order to improve the quality of health care health professionals are expected to improve their skills mainly in wound care of post sectiocaesarea either through seminars or training to provide a better service. Keywords : mobilization, wound healing, sectiocaesarea